2017
DOI: 10.1007/s00280-017-3361-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of thiopurine methyltransferase (TPMT) and multidrug resistance-associated protein gene 4 (MRP4) on mercaptopurine toxicity

Abstract: Purpose Mercaptopurine plays a pivotal role in treatment of acute lymphoblastic leukemia (ALL) and autoimmune diseases, and inter-individual variability in mercaptopurine tolerance can influence treatment outcome. Thiopurine methyltransferase (TPMT) and multi-drug resistant Protein 4 4(MRP4) have both been associated with mercaptopurine toxicity in clinical studies, but their relative contributions remain unclear. Methods We studied the metabolism of and tolerance to mercaptopurine in murine knockout models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, these mice did not show major physiologic alterations (Russel et al, 2008), indicating that MRP4 inhibition could be a feasible therapeutic approach. Also, exposition of the knockout mice to several drugs highlighted MRP4 role in the excretion of such agents, as they presented altered cytotoxicity and tissue distribution compared with wild-type animals (Leggas et al, 2004;Zamek-Gliszczynski et al, 2006;Takenaka et al, 2007;Liu et al, 2017). Moreover, several FDA-approved drugs inhibit MRP4 activity without showing any serious adverse effects (Yaneff et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these mice did not show major physiologic alterations (Russel et al, 2008), indicating that MRP4 inhibition could be a feasible therapeutic approach. Also, exposition of the knockout mice to several drugs highlighted MRP4 role in the excretion of such agents, as they presented altered cytotoxicity and tissue distribution compared with wild-type animals (Leggas et al, 2004;Zamek-Gliszczynski et al, 2006;Takenaka et al, 2007;Liu et al, 2017). Moreover, several FDA-approved drugs inhibit MRP4 activity without showing any serious adverse effects (Yaneff et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that HEI-OC1 and UB / OC-1 cells derived from the cochlea are more sensitive to cisplatin when expressing the TPMT *3A variant instead of the wild-type Tpmt 65 . In contrast, Tpmt knock-out mice do not display an increased sensitivity to cisplatin when administered at comparable levels as found in humans 66 , however this result might not be surprising given the known resistance of mice to cisplatin ototoxicity when compared to rats or guinea pigs 67 .…”
Section: Discussionmentioning
confidence: 77%
“…Pharmacogenes that encode transporters and enzymes involved in the clearance of thiopurine drugs have been in the focus, in particular ITPA and ABCC4 . The ITPA enzyme catalyzes hydrolysis of the pyrophosphate group from purine analogs triphosphates, which interferes with their incorporation into DNA [127], while the ABCC4 transporter exports thiopurine drugs and their metabolites [128]. Lower activity variants of ITPA and ABCC4 [129] genes have been associated with a diminished tolerance of thiopurine therapy, however, this is inconsistent [130,131].…”
Section: Thiopurine Drugsmentioning
confidence: 99%